ANALISIS PENDAPATAN USAHA PETERNAKAN SAPI POTONG BERBASIS SISTEM INTEGRASI DI KABUPATEN SITUBONDO - Ariani Trisna Murti; Farida Kusuma Astuti (BUANA SAINS, 2017)
The research was conducted on farmer-based system that is integrated beef cattle business with agricultural land in Situbondo. Situbondo is an agricultural area that has potential as regional business development effort of cattle with rice fields. This research was conducted in Situbondo on 5 August to 12 September 2014. The choice of location research is done intentionally (purposive) in consideration because the area is one of the fields and the majority of people work as petani.Tujuan of this study was to determine the magnitude household income of cattle on beef cattle business integration system and to determine the household income of paddy farmers' efforts. Samples were observed in this study were 39 respondents, and data analysis using the formula to determine the income analysis-cattle farmers' income, the contribution formula to determine the contribution of farming to income-livestock farmers. The results showed that revenues in the system integration business beef with rice fields Rp. 28,434,100.1. Suggestions in the study should be the ranchers and farmers of system integration in Situbondo increase to the maximum all the factors affecting the production of beef cattle business productivity, thereby automatically breeders and farmers' income will also